2007
DOI: 10.1117/1.2804931
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of time-resolved spectroscopy by measuring cerebral hemodynamics during cardiopulmonary bypass surgery

Abstract: We developed a three-wavelength time-resolved spectroscopy (TRS) system, which allows quantitative measurement of hemodynamics within relatively large living tissue. We clinically evaluated this TRS system by monitoring cerebral circulation during cardiopulmonary bypass surgery. Oxyhemoglobin, deoxyhemoglobin, total hemoglobin and oxygen saturation (SO(2)) were determined by TRS on the left forehead attached with an optode spacing of 4 cm. We also simultaneously monitored jugular venous oxygen saturation (SjvO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 40 publications
0
37
0
Order By: Relevance
“…; [20][21][22]). The oxy-Hb concentrations in the left and right prefrontal cortex were measured at 1 Hz for 10 s before (premeasurement condition) odor administration as well as during the 90 s of odor administration (postmeasurement condition).…”
Section: Methodsmentioning
confidence: 99%
“…; [20][21][22]). The oxy-Hb concentrations in the left and right prefrontal cortex were measured at 1 Hz for 10 s before (premeasurement condition) odor administration as well as during the 90 s of odor administration (postmeasurement condition).…”
Section: Methodsmentioning
confidence: 99%
“…Sensors were mounted on the participant's forehead, and oxy-Hb concentrations in the prefrontal cortex were measured by a TRS-20 system (Hamamatsu Photonics K.K., Shizuoka, Japan) [21][22][23]. The oxy-Hb concentrations in the left and right prefrontal cortex were measured before the participant touched the materials (premeasurement) and during the 90 s during which the participant touched the materials (postmeasurement).…”
Section: Physiological Measurements Trsmentioning
confidence: 99%
“…They have been validated with Monte Carlo simulations and phantoms, 15,23,24 and have been applied to monitor developmental cerebral changes in infants. 22 In adults, the TD-NIRS technology has been applied to monitor variations in brain oxygenation and blood volume during cardiopulmonary bypass surgery 25 or to detect vasospasms following subarachnoid hemorrhage. 21 Most of the in vivo studies mentioned above have relied on a simple head model described as a homogeneous semi-infinite medium.…”
Section: Introductionmentioning
confidence: 99%
“…21 Most of the in vivo studies mentioned above have relied on a simple head model described as a homogeneous semi-infinite medium. 1,[6][7][8][9][10]16,[19][20][21][22]25,26 This model has shown promising results in piglets and infants, 5,8,9,11,20,22,27 but it is widely recognized that, in the case of the adult head, its oversimplification causes strong contamination of the brain optical properties by those of the extracerebral tissue. For the FDMD approach, Franceschini et al 12 have shown, with simulations and phantom measurements in a slab geometry, that when a superficial layer thicker than ∼1 cm is present, the error on the retrieved absorption of the second layer can exceed 50%.…”
Section: Introductionmentioning
confidence: 99%